Metamorphic Zonation by Out‐of‐Sequence Thrusting at Back‐Stepping Subduction Zones: Sequential Accretion of the Caledonian Internides, Central Sweden. Issue 10 (15th October 2018) - Bender, H.; Ring, U.; Almqvist, B. S. G.; Grasemann, B.; Stephens, M. B.
Abstract: Exhumation of the high‐grade metamorphic Seve Nappe Complex and its emplacement between lower‐grade nappes has been related to wedge extrusion in the central Scandinavian Caledonides. To test this hypothesis, the kinematic evolution of the Caledonian nappe pile is studied by systematic structural mapping in central and northern Jämtland, Sweden. Structural data, combined with petrological and quartz microstructure observations, document pervasive top‐to‐the‐ESE, foreland‐directed shearing under progressively decreasing metamorphic grade across the entire nappe pile. Mylonitic foliation, foliation‐parallel boudinage, and abundant top‐to‐the‐ESE and rare, scattered top‐to‐the‐WNW shear‐sense indicators imply foreland‐directed general shear. This deformation regime caused exhumation by concurrent thrusting and vertical ductile thinning. We propose a specific succession of in‐ and out‐of‐sequence thrusts that generated the metamorphic zonation. Our model envisions in‐sequence propagation of thrusts during exhumation of the Seve Nappe Complex, related to subduction of Baltica beneath a volcanic arc within Iapetus. Concurrently, Iapetus subducted beneath Laurentia farther to the west. When Iapetus was closed, Baltica subduction stepped westward and continued beneath Laurentia. The back stepping of subduction at the onset of continental collision caused out‐of‐sequence propagation of the orogenic wedge. Thrusting cut downsection across the existing tectonostratigraphy, emplacing units of lower metamorphic grade above the high‐grade Seve Nappe Complex. This imbrication generated the present metamorphic zonation of the Caledonian nappe pile during sustained convergence between Laurentia and Baltica. Key Points: Top‐ESE shear is pervasive across the metamorphically zoned Caledonian nappe pile Mylonitic fabrics indicate sustained foreland‐directed general shear, causing exhumation by concurrent thrusting and vertical thinning Back stepping of Baltica subduction resulted in out‐of‐sequence propagation of orogenic wedge